1996
DOI: 10.1103/physrevlett.77.3288
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Entropy from Loop Quantum Gravity

Abstract: We argue that the statistical entropy relevant for the thermal interactions of a black hole with its surroundings is (the logarithm of) the number of quantum microstates of the hole which are distinguishable from the hole's exterior, and which correspond to a given hole's macroscopic configuration. We compute this number explicitly from first principles, for a Schwarzschild black hole, using nonperturbative quantum gravity in the loop representation. We obtain a black hole entropy proportional to the area, as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
634
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(670 citation statements)
references
References 15 publications
20
634
1
3
Order By: Relevance
“…Subsequent works in different formalisms for quantum gravity (especially in string theory and loop quantum gravity) have not only provided an explanation to Bekenstein's result [3,4], but also revealed that the linear behavior of the entropy should be modified by a leading order correction that is logarithmic for large areas [5,6]. Similar results have been derived also by considering general properties of black holes [7].…”
Section: Introductionsupporting
confidence: 63%
“…Subsequent works in different formalisms for quantum gravity (especially in string theory and loop quantum gravity) have not only provided an explanation to Bekenstein's result [3,4], but also revealed that the linear behavior of the entropy should be modified by a leading order correction that is logarithmic for large areas [5,6]. Similar results have been derived also by considering general properties of black holes [7].…”
Section: Introductionsupporting
confidence: 63%
“…In [19] the entropy is defined as logarithm of the number of microstates for which the sum (6) is between N and N + ∆N, N ≫ ∆N ≫ 1 (here and below the notations of the present article are used). The conclusion made in [19] is that the value of this logarithm is in the interval (0.96 − 1.38)N. However, under the only condition N ≫ 1, without any assumption made about the distribution of the angular momenta j over the edges, how can one arrive at the above numbers (0.96 − 1.38)N? The same question (in fact, objection) refers to the results obtained in [20].…”
mentioning
confidence: 99%
“…In this Letter we show how, within the tunneling framework, the presence of a quantum ergosphere can be related to the appearance of a logarithmic correction to the Bekenstein-Hawking entropyarea relation of the type emerging in different quantum gravity scenarios [8,9,10,11,12,13,14,15]. This provides a link between quantum gravity microscopic description of black holes and the origin of the quantum fluctuations responsible for the formation of the quantum ergosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of the black hole entropy in several quantum gravity scenarios [8,9,10,11,12,13,14,15], besides reproducing the familiar linear relation between area and entropy obtained a leading order "quantum" correction with a logarithmic 3 dependence on the area 4…”
Section: A Tunnel Through the Quantum Horizonmentioning
confidence: 99%